The Effectiveness of First Aid Education on Basic Life Support Knowledge and Skill Among Family Members with Heart Diseases - Pauzan Efendi; Erni Buston; Indah Nur Imamah (Jurnal Penelitian Pendidikan IPA, 2023)
An increasing mortality rate in many places including highways, workplaces, schools, or even in the home mostly occurred because of low knowledge of first aid with the proper and correct procedure. The first aid knowledge for heart diseases patient remains low among family members to prevent the worsening condition of the patients. The purpose of this study was to determine the effect of first aid education on basic life support (BLS) among family members with heart disease in Lingkar Timur Primary Health Care, Bengkulu City. The design of this study was a quasi-experiment with a pre and post-test. Totally 40 respondents who contributed to this study who selected by simple random sampling. The intervention has been done by giving the demonstration, and audio-visual knowledge about basic life survey (BLS). The average age of the respondents was 30.23 years, more than half of the respondents were female by 26 people (65%), and more than half of the respondents graduated from senior high school by 21 people (52.5%). Most of the respondents work as an entrepreneur by 10 people (25%). Most of the respondents' income was <Rp 1,000,000 by 16 people (40%). The results showed that there was an effect of education with audio-visual and BLS demonstration on the skills of doing BLS (p-value 0.000 < 0.05). Training effects increasing the knowledge and skills of BLS respondents. Emergency training needs to be given to all people as a form of early awareness of emergency conditions